Mucinous Cystadenoma of the Appendix - Çobanoğlu, Bengü; Yekeler, Hayreddin (Fırat University, 2002)
Mucinous Cystadenoma of the appendix are uncommon and are rarely diagnosed prior to operation. Generally, the term" mucocele" refers to a lesion of the appendix with a dilated lumen or cystic mass that is filled with mucin. In this study, a case of mucinous cystadenoma of the appendix was in a 65 years old patient presented because of rarity.

Apendiksin müsinöz kistadenomu seyrek görülür ve nadiren operasyon öncesi teşhis edilir. Genellikle "mukosel" olarak isimledirilen bu lezyon, müsin ile dolu dilate bir lümen veya kistik bir kitledir. Bu çalışmada 65 yaşındaki bir hastada saptanan apendiksin müsinöz kistadenomu ender görülmesi nedeniyle sunulmuştur.
APENDİKSİN MÜSİNÖZ KİSTADENOMU